2019
DOI: 10.1111/apt.15389
|View full text |Cite
|
Sign up to set email alerts
|

Letter: psoriasiform eruption during vedolizumab therapy

Abstract: Linked ContentThis article is linked to Chaparro et al paper. To view these articles, visit https://doi.org/10.1111/apt.15930.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A German study found 26 skin-related adverseevents in 212 patients (12%) who received vedolizumab; more than half of these cases consisted of acne. 2 Psoriasiform dermatitis was observed in three case reports;[3][4][5] lesions resolved in two cases after vedolizumab cessation 3,5. Our case was unique with its pediatric onset and resolution of eruption with topical treatment.The mechanism underlying the development of psoriasiform dermatitis remains unclear.…”
mentioning
confidence: 99%
“…A German study found 26 skin-related adverseevents in 212 patients (12%) who received vedolizumab; more than half of these cases consisted of acne. 2 Psoriasiform dermatitis was observed in three case reports;[3][4][5] lesions resolved in two cases after vedolizumab cessation 3,5. Our case was unique with its pediatric onset and resolution of eruption with topical treatment.The mechanism underlying the development of psoriasiform dermatitis remains unclear.…”
mentioning
confidence: 99%